2023
DOI: 10.3389/fcimb.2023.1059603
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immunization with pneumococcal surface protein A provides the immune memories of offspring against pneumococcal infection

Abstract: IntroductionStreptococcus pneumoniae (S. pneumoniae) is one of the most widespread pathogens in the world and one of the largest infectious causes of infant mortality. Although current vaccines have various benefits, antibiotic resistance and the inability to vaccinate infants less than one year old demands the development of new protective strategies. One strategy, ‘maternal immunization’, is to protect infants by passive immunity from an immunized mother, although its mechanism is still not fully understood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(63 reference statements)
0
0
0
Order By: Relevance
“…As a consequence, these surface proteins can be highly immunogenic, representing a suitable target for further vaccine development. Preliminary results of murine models confirmed that the vaccine against PspA induced sufficient antibody response, and the levels of anti-PspA IgG in the offspring sera derived from immunized mothers was significantly higher compared to those in the offspring from sham-immunized mothers [ 80 , 81 ]. A recombinant PspA-based vaccine (PspAB1-5) showed efficacy in modifying complement-mediated killing through the deposit of more C3 complement components on the surface of the S. pneumoniae strain [ 82 ].…”
Section: Main Virulence Factors Of S Pneumoniae An...mentioning
confidence: 98%
“…As a consequence, these surface proteins can be highly immunogenic, representing a suitable target for further vaccine development. Preliminary results of murine models confirmed that the vaccine against PspA induced sufficient antibody response, and the levels of anti-PspA IgG in the offspring sera derived from immunized mothers was significantly higher compared to those in the offspring from sham-immunized mothers [ 80 , 81 ]. A recombinant PspA-based vaccine (PspAB1-5) showed efficacy in modifying complement-mediated killing through the deposit of more C3 complement components on the surface of the S. pneumoniae strain [ 82 ].…”
Section: Main Virulence Factors Of S Pneumoniae An...mentioning
confidence: 98%